Unpacking the metrics: a critical analysis of the 2025 QS World University Rankings using Australian university data - MD Badiuzzaman (Frontiers in Education, 2025)
Despite extensive critiques of university rankings highlighting their emphasis on reputation metrics over teaching quality and equity, empirical validation remains limited. This study addresses this gap by analysing relationships between QS World University Rankings indicators and overall scores for Australian universities (2025 dataset). Using correlational analyses on publicly available data, the findings identify Academic Reputation, Employer Reputation, and Employment Outcomes as influential metrics, while Faculty-to-Student Ratio and Sustainability show limited or negative correlations. Results further suggest systemic biases favouring larger, research-intensive institutions, potentially disadvantaging smaller or specialised universities regardless of academic quality. Although focused on the Australian higher education context, this research contributes timely empirical insights relevant globally. The findings inform university leaders, policymakers, and scholars, providing evidence to critically evaluate ranking methodologies and advocating for transparent, equitable, and pedagogically inclusive approaches to assessing institutional excellence.